Inverse relationship between altitude and cardiometabolic risk in the Peruvian population: results of a population-based survey and the importance of waist-to-height ratio as an indicator of cardiometabolic risk - Zela-Coila, Frank (2023)
Presentation: This article presents our critical appraisal of an observational study published in the International Journal of Environmental Research and Public Health in 2022. Conclusions of the Study: An inverse association was identified between living at higher altitudes and the level of cardiometabolic risk in the Peruvian adult population. However, the prevalence of cardiometabolic risk in the different altitude categories evaluated remains above 82% (80.9 - 84.6), which represents a large proportion of the population at risk at every altitude. Critical comment: The study is relevant because of the use of the waist-height ratio, considered an anthropometric indicator with greater precision for estimating cardiometabolic risk, being a study with a low risk of bias, and having national representativity. In addition, it is important because the waist-height ratio is inexpensive and easy to use. It is also superior to BMI and ideal for application in Peru. In addition, the general conclusion of the study is valid; however, the lack of evaluation of temporality due to the same characteristic of the study (cross-sectional study) and the residual bias that it has by not evaluating some variables, makes it necessary to carry out a longitudinal study to be able to support the results of the study. The present critical review finds internal validity in the results of the study, but at the moment they would not be applicable to generalize to the entire population due to the residual bias.